Peran Kepemimpinan dalam Meningkatkan Employee Well-Being: Systematic Literature Review - Amelia Nanda Basri; Aurelia Khairunnisa; Jesklin Clara G.B; Rika Ningsih; Satriadi (Universitas Sarjanawiyata Tamansiswa, 2026)
Employee well-being is an increasingly pressing strategic issue in the contemporary workplace, particularly in the wake of the COVID-19 pandemic. This study aims to identify and understand the role of leadership in enhancing employee well-being in the workplace. The method used is a Systematic Literature Review (SLR) of 20 scientific articles obtained from the Google Scholar academic database as well as relevant national and international journals, published within the last five years. The findings indicate that various leadership styles transformational, ethical, inclusive, servant, and virtuous have been proven to have a positive and significant impact on employee well-being. Effective leadership can enhance job satisfaction, reduce stress, strengthen employee engagement, and create a supportive and adaptive work environment. Conversely, negative and authoritarian leadership styles have a detrimental impact on employees’ psychological well-being. These findings reinforce that human-centered leadership strategies are key to achieving optimal employee well-being and driving overall organizational performance.